The Effect of Family Ownership and Control on Dividend Policy of Publicly Listed Firms in Indonesia and Malaysia - Ayu, Laras; Viverita, Viverita (UI Scholars Hub, 2020)
The purpose of this study is to determine the influence of family ownership and family control ona firm’s dividend policy of publicly listed firms in Indonesia and Malaysia. This study applied thegeneralized least square panel data over 2003-2016 and considering the period of global financialcrisis 2008-2010. The results show that a firm with a higher percentage of family ownership paysmore dividend compared to non-family firms. The same effect applies to the percentage of familycontrol. In contrast, we found that higher debt levels will reduce the dividend payment. These findingsindicate that dividend distribution can be used as a policy to lessen agency problems of listed firms.